Effects of As2O3 and Resveratrol on the Proliferation and Apoptosis of Colon Cancer Cells and the hERG-mediated Potential Mechanisms - Yan, Caichuan; Li, Fengmei; Zhang, Yuhao; Li, Yang; Li, Mingzhu; Wang, Fang; Zhang, Guocui; Li, Yuexin; Li, Baoxin; Zhao, Xin (Current Pharmaceutical Design, 2019)
Background: As2O3 and resveratrol have been widely considered to be effective in anti-cancer therapies and the underlying mechanisms have been reported extensively. However, the combined treatment effect and potential target of As2O3 and resveratrol in the treatment of tumors remains elusive. The purpose of this study was to investigate the benefits and efficacy of As2O3 in combination with resveratrol in the treatment of colon cancer, as well as looking for new targets that could provide alternative explanation of the efficacy of drugs. Methods: The proliferation of cancer cells was measured by the MTT and EdU staining assay, while the apoptosis of cancer cells was determined by the flow cytometry. Western blot and immunoprecipitation were performed to measure the expression levels of proteins and the interaction between hERG and integrin β1, respectively. Results: In this study, we found that both As2O3 and resveratrol can effectively inhibit cell proliferation and promote cell apoptosis in colon cancer, and the combined effect of the two drugs on colon cancer cells is more preeminent. The combination of As2O3 with resveratrol, on the one hand reduced the expression of hERG channels on the membrane, and on the other hand weaken the binding between hERG and integrin β 1, which may be the main cause of downstream signaling pathways alterations, including the activation of the apoptotic pathway. Conclusion: Taken together, hERG, as a subunit of potassium ion channel on the cell membrane, is highly likely to be involved in the As2O3 and resveratrol induced intracellular signaling cascade disorder, and this novel signaling pathway that sustains the progression of colon cancer may be a promising therapeutic target for human colon cancer treatment in the future.
Keywords: hERG